Uji Efektivitas Antibakteri Ekstrak Etanol 96% Tanaman Gonda (Sphenoclea zeylanica Gaertn) terhadap Staphylococcus aureus - Pande I Ketut Sukadiasa; Ni Putu Wintariani; I Gusti Ngurah Agung Windra Wartana Putra (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Staphylococcus aureus is a gram-positive bacterium that is the leading cause of infections of the skin, soft tissue, respiratory tract, bones, and joints. The use of traditional medicine is generally considered safer than the use of modern medicine. One of the plants in Indonesia that can be used as medicine is the Gonda plant (Sphenoclea zeylanica Gaertn). The phytochemical compounds in the gonda plant are saponins, flavonoids, phenols, alkaloids, and steroids, which have antibacterial activity. This study aims to determine the content of secondary metabolites and the antibacterial activity of 96% ethanol extract of Gonda plants with different concentration variations against Staphylococcus aureus bacteria. This research is quantitative research with an experimental research design. The results showed that the 96% ethanol extract of the gonda plant contained flavonoids, saponins, tannins, steroids, and alkaloids and showed antibacterial activity. The average inhibition zone concentration of the extract was 5%, 10%, 15%, and 20%, respectively, 9.4 ± 0.19 mm, 12.56 ± 0.18 mm, 14.63 ± 0.30 mm, 17.45 ± 0.36 mm in the medium to strong category. There was a significant difference (P<0.05) between the inhibition zone values of each concentration, where the increase in the inhibition zone value was directly proportional to the increase in the extract concentration. The extract with a concentration of 20% had an immense inhibition zone value of 17.45 mm.